(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
This study examines the literature on the usefulness of nano-photocatalysts in the synthesisof organic molecules via fine chemical synthesis. Current laboratory and industrial methods forpreparing organic molecules are extremely dependent on nonrenewable energy sources. Additionally,these conventional procedures typically necessitate conditions of severe temperature and pressure. Inrecent years, there has been a change in emphasis toward photocatalysis due to a greater worldwideawareness of the need to conserve nonrenewable sources of energy. Photocatalysts have been known tocatalyse numerous organic reactions, including oxidation, reduction, addition, cyclization, andbreakdown, for quite some time. The development of nanotechnology enabled the downscaling of thesephotocatalytic materials from bulk to nanoscale, hence expanding their use and efficacy. Advances inmaterial chemistry and nanotechnology have also made it possible to produce nano-photocatalysts ofnovel types, whose molecular characteristics can be tailored and controlled. In this review, an attempthas been made to categorise these various nanophotocatalysts based on their composition andmechanism. Under UVvisible irradiation, these nanomaterials can be employed for a variety of organictransformations, as highlighted in the review. Nanophotocatalysts have considerable potential for theeco-friendly synthesis of extremely valuable chemical molecules. We trust that this review is accuratecan provide insights into research done in this field so far, which can pave way for further progress inthis topic of far-fetched social significance.